Body composition and perception of teenagers from public schools - Ana Paula Araújo Ferreira; Júlia Aparecida Devidé Nogueira; Ingrid Wiggers; Keila Elizabeth Fontana (Desafio Singular, 2013)
Adolescence is accompanied by cognitive, emotional, social and biological changes; situations that increase the risk for development of psychosomatic disorders. This study measured and classified body composition and compared it to body self-perception in adolescents. Students from the seventh to ninth grade in public primary education in Distrito Federal, Brazil, answered socio-demographic and body self-perception questionnaires. Weight and height were measured and body mass index (BMI) was calculated for body composition classification. From the 977 adolescents, 79.1% presented eutrophic BMI. Of the 473 boys, 11.4% were overweight and 4.7% underweight, 23.8% perceived the body as smaller than it really is and 25.5% tried to gain body mass. Of the 504 girls, 11.9% were overweight and 13.4% underweight, 24.1% perceived the body as larger than it really is and 32.5% tried to lose body mass. Inadequate body composition, prevalent in 20.9% of adolescents, may harm growth, development and health. These problems may be aggravated by the high prevalence of distorted body self-perception and attitudes for bodily changes. It is recommended the implementation of educational interventions on body composition, perception and culture and health, with different approaches by gender.